Amino Acids and Peptides Organocatalysts: A Brief Overview on Its Evolution and Applications in Organic Asymmetric Synthesis - Kamanna, Kantharaju (Current Organocatalysis, 2021)
This review highlights the application of biopolymers of natural α-amino acids and its derived wild-type peptides employed as organocatalysts for the asymmetric synthesis of various important compounds published by researchers across the globe. The α-amino acid with L-configuration is available commercially in the pure form and plays a crucial role in enantioselective chiral molecule synthesis. Out of twenty natural amino acids, only one secondary amine-containing proline amino acid exhibited revolution in the field of organocatalysis because of its rigid structure and the formation of an imine like transition state during the reaction, which leads to more stereoselectivity. Hence, it is referred to as a simple enzyme in organocatalyst. Chiral enantioselective organic molecule synthesis has been further discussed by employing oligopeptides derived from the natural amino acids as a robust biocatalyst that replaced enzyme catalysts. The di-, tri, tetra-, penta- and oligopeptide derived from the natural amino acids are demonstrated as a potential organocatalyst, whose catalytic activity and mechanistic pathways are reviewed in the present paper. Several choices of organocatalyst are developed to achieve a facile and efficient stereoselective synthesis of many complex natural products with optically pure isomer. Subsequently, the researcher developed green and sustainable heterogeneous catalytic system containing organocatalyst immobilized onto solid inorganic support or porous material for accelerating reaction rate with asymmetric one isomer product through the heterogeneous phase. Further, researchers developed heterogeneous organocatalysts-Metal-Organic Frameworks (MOFs) that emerged as alternative simple and facile heterogeneous catalysts for the bulk production and flow reactor for enantioselective synthesis. This review compiled many outstanding discoveries in organocatalysts derivative of amino acids, peptides and heterogenized-MOFs employed for many organic transformations in research and industrial applications.
Keywords: enantioselectivity